Characterization of the GDP-D-Mannose Biosynthesis Pathway in Coxiella burnetii: The Initial Steps for GDP-β-D-Virenose Biosynthesis - Narasaki, Craig T.; Mertens, Katja; Samuel, James E. (PLOS ONE, 2011)
Coxiella burnetii, the etiologic agent of human Q fever, is a Gram-negative and naturally obligate intracellular bacterium. The O-specific polysaccharide chain (O-PS) of the lipopolysaccharide (LPS) of C. burnetii is considered a heteropolymer of the two unusual sugars β-D-virenose and dihydrohydroxystreptose and mannose. We hypothesize that GDP-D-mannose is a metabolic intermediate to GDP-β-D-virenose. GDP-D-mannose is synthesized from fructose-6-phosphate in 3 successive reactions; Isomerization to mannose-6-phosphate catalyzed by a phosphomannose isomerase (PMI), followed by conversion to mannose-1-phosphate mediated by a phosphomannomutase (PMM) and addition of GDP by a GDP-mannose pyrophosphorylase (GMP). GDP-D-mannose is then likely converted to GDP-6-deoxy-D-lyxo-hex-4-ulopyranose (GDP-Sug), a virenose intermediate, by a GDP-mannose-4,6-dehydratase (GMD). To test the validity of this pathway in C. burnetii, three open reading frames (CBU0671, CBU0294 and CBU0689) annotated as bifunctional type II PMI, as PMM or GMD were functionally characterized by complementation of corresponding E. coli mutant strains and in enzymatic assays. CBU0671, failed to complement an Escherichia coli manA (PMM) mutant strain. However, complementation of an E. coli manC (GMP) mutant strain restored capsular polysaccharide biosynthesis. CBU0294 complemented a Pseudomonas aeruginosa algC (GMP) mutant strain and showed phosphoglucomutase activity (PGM) in a pgm E. coli mutant strain. Despite the inability to complement a manA mutant, recombinant C. burnetii PMI protein showed PMM enzymatic activity in biochemical assays. CBU0689 showed dehydratase activity and determined kinetic parameters were consistent with previously reported data from other organisms. These results show the biological function of three C. burnetii LPS biosynthesis enzymes required for the formation of GDP-D-mannose and GDP-Sug. A fundamental understanding of C. burnetii genes that encode PMI, PMM and GMP is critical to fully understand the biosynthesic pathway of GDP-β-D-virenose and LPS structure in C. burnetii.